Rethinking systemic change in practice - perspectives from NUTEC-MD in northern Uganda - Koleros, Andrew (BEAM Exchange, 2016)
Document description This document is currently being finalised and will be published shortly. Please try again soon. Recent research by The BEAM Exchange seeks to understand theoretical perspectives on how market systems approaches can contribute to inclusive economic development through systemic change. It produced three main insights. Economies are evolving systems, building on the mechanisms of variety creation, selection and amplification. Current economic performance, including aspects like the inclusiveness of growth and economic evolution, are shaped by the ability of a society to explore different options for institutional arrangements and adjust them over time. This process of evolution is complex. While some aspects can be designed and managed, others need to be explored through a process of learning and adjustment. This paper responds to these insights by providing a practitioner perspective through the lens of one programme: “Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD)”, implemented by Palladium Group. It begins with a brief introduction to the programme and key aspects of its design phase. It then provides a summary of the three main research insights, with reflections on their applicability for programme design based on the NUTEC-MD experience. Finally, it provides some conclusions for the wider practitioner community based on this case.

The guiding logics and principles for designing emergent transdisciplinary research processes: learning experiences and reflections from a transdisciplinary urban case study in Enkanini informal settlement, South Africa - van Breda, John; Swilling, Mark (Sustainability Science, 2019)
Transdisciplinarity is not a new science per se, but a new methodology for doing science with society. A particular challenge in doing science with society is the engagement with non-academic actors to enable joint problem formulation, analysis and transformation. How this is achieved differs between contexts. The premise of this paper is that transdisciplinary research (TDR) methodologies designed for developed world contexts cannot merely be replicated and transferred to developing world contexts. Thus a new approach is needed for conducting TDR in contexts characterised by high levels of complexity, conflict and social fluidity. To that end, this paper introduces a new approach to TDR titled emergent transdisciplinary design research (ETDR). A core element of this approach is that the research process is designed as it unfolds, that is, it transforms as it emerges from and within the fluid context. The ETDR outlined in this paper emerged through a case study in the informal settlement (slum) of Enkanini in Stellenbosch, South Africa. This case study demonstrates the context from and within which the ETDR approach and identifies a set of guiding logics that can be used to guide ETDR approaches in other contexts. The study demonstrates that the new logics and guiding principles were not simply derived from the TDR literature, but rather emerged from constant interacting dynamics between theory and practice. Learning how to co-design the research process through co-producing transformative knowledge and then implementing strategic interventions to bring about incremental social change is key to theory development in ways that are informed by local contextual dynamics. There are, however, risks when undertaking such TDR processes such as under-valuing disciplinary knowledge, transferring risks onto a society, and suppressing ‘truth-to-power’.

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.

Applying Systems Thinking to Education: The RISE Systems Framework - Spivack, Marla (Research on Improving Systems of Education (RISE), 2021)
Many education systems in low- and middle-income countries are experiencing a learning crisis. Many efforts to address this crisis do not account for the system features of education, meaning that they fail to consider the ways that interactions and feedback loops produce outcomes. Thinking through the feedback relationships that produce the education system can be challenging. The RISE Education Systems Framework, which is sufficiently structured to give boundaries to the analysis but sufficiently flexible to be adapted to multiple scenarios, can be helpful. The RISE Framework identifies four key relationships in an education system: politics, compact, management, and voice and choice; and five features that can be used to describe these relationships: delegation, finance, information, support, and motivation. This Framework can be a useful approach for characterising the key actors and interactions in the education system, thinking through how these interactions produce systems outcomes, and identifying ways to intervene that can shift the system towards better outcomes.

Getting Real about Unknowns in Complex Policy Work - Andrews, Matt (Research on Improving Systems of Education (RISE), 2021)
As with all public policy work, education policies are demanding. Policy workers need to ‘know’ a lot—about the problems they are addressing, the people who need to be engaged, the promises they can make in response, the context they are working in, and the processes they will follow to implement. Most policy workers answer questions about such issues within the structures of plan and control processes used to devise budgets and projects. These structures limit their knowledge gathering, organization and sense-making activities to up-front planning activities, and even though sophisticated tools like Theories of Change suggest planners ‘know’ all that is needed for policy success, they often do not. Policies are often fraught with ‘unknowns’ that cannot be captured in passive planning processes and thus repeatedly undermine even the best laid plans. Through a novel strategy that asks how much one knows about the answers to 25 essential policy questions, and an application to recent education policy interventions in Mozambique, this paper shows that it is possible to get real about unknowns in policy work. Just recognizing these unknowns exist—and understanding why they do and what kind of challenge they pose to policy workers—can help promote a more modest and realistic approach to doing complex policy work.